Some Aspects of Legal Regulation of the Dismissal from Work: Features, Types and Social Guarantees (Law and Safety, 2021)
Based on the analysis of the norms of general and special labor legislation of Ukraine, the author has researched the problem of legal regulation of one of the preventive measures of labor law – dismissal from work. The procedure of dismissal from work within the mechanism of legal regulation mainly performs a preventive function. The problem of dismissal from work in labor law has not been studied enough. A number of provisions regulating the relationship that has developed in case of dismissal are scattered across various regulatory acts. Some of those relationships are not regulated at all.Dismissal is often equated with the transfer, removal or displacement. In this case employees’ labor rights and guarantees are violated.It has been found out that the institution of dismissal from work at the present historical stage of development has its own characteristics of normative regulation. To date, neither labor law nor caselaw has agreed on a single generally accepted definition of the term of “dismissal from work”.Based on the study of scientific views of scholars and taking into account the analysis of the norms of general labor legislation, the main characteristics of the definition of “dismissal from work” have been identified. It has been found out that the definition of “dismissal from work” differs from “deprivation of office”; the author has studied the features of “dismissal from work”, types and social guarantees for employees at the time of dismissal.It has been noted that dismissal from work is atypical legal measure that employers apply to employees in some cases within labor law. It has temporary nature, it is intended to prevent the employee from work, it can be applied both through the fault of the employee and without the fault of the employee, it is usually free of charge.It has been emphasized that there is a need to develop and adopt a normative act, which should clearly define the cases of dismissal, its tasks and objectives, procedure and consequences of application. It is also necessary to enshrine guarantees of observance of employees’ rights at the time of dismissal in regulatory acts.
Keywords: labor legislation; legal regulation; dismissal from work; deprivation of office; National Police of Ukraine; features of the dismissal from work.